Variable speed drives programming controllers - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
The VARIABLE SPEED DRIVES: Programming Controllers training program, or unit, is designed to familiarize trainees with the basic principles of programming controllers for variable speed DC and AC motors. After completing this program, the trainees should be able to identify and describe common parameters that may have to be programmed for a DC variable speed controller and for an AC variable speed controller. They should also be able to describe additional programming that may be required when an AC variable speed controller is set up for flux vector operation.
Keywords: Variable speed drives; Electric driving